Baicalin enhances respiratory mucosal immunity by modulating antiviral protein expression and T-cell homeostasis during H9N2 infection - Liu, Zhenyi; Guo, Haotong; Zhi, Yan; Jiang, Xiaorui; Zhang, Qian (Frontiers in Immunology, 2025)
IntroductionThe H9N2 avian influenza virus, although not highly pathogenic, still poses ongoing risks to poultry health and food security due to its ability to resist vaccines and its potential to spread to humans.MethodsThis study investigated the effects of baicalin, a flavonoid derived from Scutellaria baicalensis, on respiratory mucosal immunity during H9N2 infection. In vitro experiments were conducted using MLE-12 alveolar epithelial cells, and in vivo evaluations were performed in a mouse model of H9N2 infection.ResultsBaicalin treatment enhanced the expression of antiviral proteins Mx1 and PKR in a dose- and time-dependent manner, helping to counteract the virus’s suppression of these defense proteins. In addition to strengthening this epithelial barrier, baicalin has both antiviral and immune-regulating effects: it directly blocks viral replication and helps restore the CD4+/CD8+ T cell ratio in H9N2-infected mice. Most importantly, baicalin reduces lung damage and spleen shrinkage while keeping the immune system balanced. These results show that baicalin enhances mucosal antiviral defenses by simultaneously regulating innate antiviral pathways (Mx1 and PKR) and restoring adaptive immune balance (CD4+/CD8+ T-cell ratio).DiscussionThese dual protective effects highlight baicalin’s potential as a natural therapeutic strategy for improving mucosal immunity against vaccine-resistant influenza viruses such as H9N2, contributing valuable insights into plant-derived immunomodulatory approaches against emerging zoonotic viral threats.